Pengaruh Teknologi Informasi Dan Kualitas Layanan Terhadap Kepuasan Nasabah Bank BCA Cabang KCU Tanjung Priok - Naufaliani, Nabila; Widyawan, Bisma (JAMBIS : Jurnal Administrasi Bisnis, 2025)
In recent years, Bank BCA Tanjung Priok branch has experienced obstacles and problems in every service, resulting in customer complaints and a decrease in the number of customers who transact directly to the branch and an increase in the number of customers who transact digitally. This is related to information technology and service quality. This study aims to test and analyze the influence of information technology and service quality on customer satisfaction at Bank BCA Tanjung Priok branch. Respondents in this study were customers of Bank BCA Tanjung Priok branch. The research method used is a quantitative method. The sampling technique used a random sampling method with a sample size of 100 respondents. Based on the analysis conducted, this study shows that